QuilA-Adjuvanted T. gondii Lysate Antigens Trigger Robust Antibody and IFNγ+ T Cell Responses in Pigs Leading to Reduction in Parasite DNA in Tissues Upon Challenge Infection - Rahman, Mizanur; Devriendt, Bert; Gisbert Algaba, Ignacio; Verhaegen, Bavo; Dorny, Pierre; Dierick, Katelijne; Cox, Eric (Frontiers in Immunology, 2019)
Toxoplasma gondii is an intracellular parasite of all mammals and birds, responsible for toxoplasmosis. In healthy individuals T. gondii infections mostly remain asymptomatic, however this parasite causes severe morbidity and mortality in immunocompromised patients and congenital toxoplasmosis in pregnant women. The consumption of raw or undercooked pork is considered as an important risk factor to develop toxoplasmosis in humans. Since effective therapeutic interventions to treat human toxoplasmosis are scarce, vaccination of meat producing animals may prevent T. gondii transmission to humans. Here, we evaluated the elicited immune responses and the efficacy of a potential vaccine candidate, generated by size fractionation of T. gondii lysate proteins, to clear parasites from experimentally T. gondii infected pigs as compared to vaccination with total lysate antigens (TLA). Our results show that both the vaccine candidate and the TLA immunization elicited strong serum IgG antibody responses and elevated percentages of CD4+CD8+IFNγ+ T cells and CD3-CD8+IFNγ+ NK cells in T. gondii infected pigs. However, the TLA vaccine induced the strongest immune response and reduced the parasite load below the detection limit in most tissues. These findings might inform the development of novel vaccines to prevent T. gondii infections in livestock species and humans.